THE USE OF FLIPBOOK MEDIA WITH GAME-BASED LEARNING TO IMPROVE STUDENTS’ COMPREHENSION OF ARGUMENTATIVE TEXTS - Ari Ferdianto; Agus Yuwono; Panca Dewi Purwati (Jurnal Cakrawala Pendas, 2025)
Understanding argumentative texts is an important competency in Indonesian language learning in elementary school, but many students still have difficulty understanding the structure. This study examines the effectiveness of using flipbook media integrated with a game-based learning approach to improve students’ comprehension of argumentative texts. A mixed-methods sequential explanatory design was applied. Quantitative data were collected through a one-group pretest-posttest involving 20 fourth-grade students at SD Negeri 1 Ngareanak and analyzed using paired sample t-tests. Qualitative data were obtained from classroom observations and semi-structured interviews, then analyzed thematically to enrich the findings. Results indicated significant improvement in students’ comprehension scores, as well as increased motivation, engagement, and confidence in expressing ideas. The flipbook’s interactive features and visual elements supported clearer understanding and a more enjoyable learning process. These findings support the development of similar interactive media to improve other language skills at various levels of education.